(untitled) (Academia Journal of Medicine, 2024)
The integration of artificial intelligence (AI) in the field of dentistry has been gaining prominence, with Chatbot Generative Pretrained Transformer (ChatGPT), emerging as a pivotal tool. ChatGPT’s applications span a myriad of functionalities including diagnostic aid, educational support, and patient interaction.